LITERATURE ANALYSIS ON HIGH SCHOOL CHEMISTRY PRACTICUM METHODS: A COMPARATIVE STUDY OF VIDEO-BASED DEMONSTRATION APPROACH AND STUDENT WORKSHEETS IN THE FORMATION OF SCIENTIFIC ATTITUDES - Purba, Christina (Antis-Publisher, 2025)
Objective: The study aims to evaluate the characteristics, advantages, and disadvantages of each approach, as well as identify their impact on the development of students' scientific attitudes, such as curiosity, rigor, critical thinking, and scientific responsibility. Method: This study is a literature analysis that compares two approaches in chemistry practicum at the high school level, namely video-based demonstrations and the use of Student Worksheets (LKS), in relation to the formation of scientific attitudes. Results: The analysis showed that the video approach excelled in visualization and learning efficiency, while the LKS was more effective in developing procedural skills and scientific attitudes based on hands-on experience. The integration of the two approaches is considered capable of creating a holistic learning experience, especially in the context of inquiry-based learning. This research also emphasizes the importance of the teacher's role as a facilitator in managing adaptive practicum, as well as the need for instructional design that encourages students' independent reflection and exploration. Novelty: These findings are expected to be the basis for the development of innovative and contextualized chemistry learning methods, as well as supporting educational policies that lead to more effective and meaningful science learning.